HIGH INFLUENCE OF WATER AND ENVIRONMENTAL QUALITY ON RESPONSE, BEHAVIOUR AND GROWTH BATAK FISH FRY (Neolissochilus thienemanni) - Anne Rumondang; Muhammad Aidil Huda J.; Muhammad Latiful Khobir; Mutiaragusti Mutiaragusti (Jurnal Perikanan Unram, 2024)
Batak fish (Neolissochilus thienemanni) is an endemic species that has important ecological, economic, and cultural values for the local people of North Sumatra. However, the population of this fish has experienced a drastic decline due to environmental factors such as water quality, climate change, and pressure from human activities, such as overfishing and water pollution. One of the important aspects in Batak fish cultivation is environmental conditions, especially water height or water depth factors. Water height plays a big role in determining the quality of fish habitats, including water temperature, dissolved oxygen levels. The purpose of this study is to determine the effect of water height variations on the response, behavior and growth of Batak fish in the aquaculture environment. The study was conducted with an experimental design using a Complete Random Design (CRD) consisting of three water height treatments: 15 cm, 20 cm, and 25 cm. Observations were made every 10 days to measure the weight, length of fish, and water quality. The results showed that the water height had a significant influence on the growth of the weight and length of Batak fish. Treatment with a water height of 25 cm indicates optimal growth, while treatment with a water height of 15 cm and 20 cm indicates lower growth. The results of the study obtained where the P3 treatment (25 cm) provided the average value of the growth rate of both weight and absolute length of the highest per treatment. In other words, the average P3 is different from P1 and P2. The water level of different cultivation media affects the total water volume and movement space for Batak fish in the same cultivation container on the aquatic environmental conditions and behavior of Batak fish.